2010
DOI: 10.1002/bio.1221
|View full text |Cite
|
Sign up to set email alerts
|

Upconverted photoluminescence in Ho3+ and Yb3+ codoped Gd2O3 nanocrystals with and without Li+ ions

Abstract: The upconversion photoluminescence of Ho(3+) ion sensitized by Yb(3+) ion in Ho(3+)/Yb(3+) codoped Gd(2)O(3) nanocrystals with and without Li(+) is investigated in this paper. Strong fluorescence in the green (534-570 nm) and red (635-674 nm) regions of the spectrum has been observed, arising from the (5)F(4)/(5)S(2) → (5)I(8) and (5)F(5) → (5)I(8) transitions of Ho(3+) ion, respectively. Yb(3+) ion is considered to be a better sensitizer for catching enough pumping energy and transferring considerable energy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…[148][149][150] Recently, several research groups, including our own, have used Li + ions to further enhance the luminescence of lanthanide ions doped in this matrix. [56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74] Table 3 summarizes the concentrations of different activator (lanthanide) ions and Li + ions to obtain the optimum luminescence. The table also describes the mode of luminescence measurement (e.g.…”
Section: Effect Of LImentioning
confidence: 99%
“…[148][149][150] Recently, several research groups, including our own, have used Li + ions to further enhance the luminescence of lanthanide ions doped in this matrix. [56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74] Table 3 summarizes the concentrations of different activator (lanthanide) ions and Li + ions to obtain the optimum luminescence. The table also describes the mode of luminescence measurement (e.g.…”
Section: Effect Of LImentioning
confidence: 99%
“…42,46,49,[52][53][54][55][56][57][58][59][60][61] In addition, Li + may act as a charge compensating ion when Ln 3+ replace non-trivalent cations. 41,62 Another explanation for the upconversion emission enhancement is an increased lifetime of the intermediate excited states of the activator ions (Table S1 in ESI). 61,[63][64][65][66][67][68][69][70][71] The aforementioned mechanisms for Li + -enhanced upconversion in various hosts, including Y2O3 nanocrystals, are essentially speculative.…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, the studies often disregard both Li + elemental analysis, and careful luminescence quantum yield measurements (see Table S1 in ESI). 30,31,36,37,42,43,49,52,53,[59][60][61][62]67,69,[72][73][74][75][76][77][78][79] For instance, we found that a co-precipitation synthesis procedure, 31 comprising washing and centrifugation steps results in Li + free Y2O2 nanoparticles. In fact, the presumed Li + -doped upconversion materials obtained via solution synthesis methods have not been assessed by elemental analysis and may not contain any lithium, exception for a few studies.…”
Section: Introductionmentioning
confidence: 99%
“…64 Moreover, the versatile Li + -doping approach for enhancing UCL of UCNPs has been widely applied in various host materials, including fluorides, oxides, phosphates, molybdates, vanadates, titanates, tungstates, etc. [65][66][67][68][69][70][71][72][73] Another non-RE 3+ that should be highlighted is Mn 2+ ion, which possesses a unique 4 T 1 level. It can act as an intermediate level that helps to control the energy transfer between Er 3+ and Mn 2+ , thereby facilitating the red UC emission of Er 3+ ions.…”
Section: Impurity Dopingmentioning
confidence: 99%